(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In the midst of the COVID-19 pandemic, currently and formerly incarcerated people in the state of Michigan in the United States are partnering with writers and artists in the free world to make themselves more visible in this moment of crisis. This article looks at three case studies (the MYLIFEMATTERSTOO newsletter, the Living on Loss of Privileges web series, and correspondence programming at the Prison Creative Arts Project) in which people in prison and those who have been recently released are using their creativity and networks of supporters to assert their voices and rights. In doing so, they insist that they are citizens actively participating in free world communities.